Balanced activities of Hsp70 and the ubiquitin proteasome system underlie cellular protein homeostasis - Jawed, Areeb; Ho, Chi-Ting; Grousl, Tomas; Shrivastava, Aseem; Ruppert, Thomas; Bukau, Bernd; Mogk, Axel (Frontiers in Molecular Biosciences, 2023)
To counteract proteotoxic stress and cellular aging, protein quality control (PQC) systems rely on the refolding, degradation and sequestration of misfolded proteins. In Saccharomyces cerevisiae the Hsp70 chaperone system plays a central role in protein refolding, while degradation is predominantly executed by the ubiquitin proteasome system (UPS). The sequestrases Hsp42 and Btn2 deposit misfolded proteins in cytosolic and nuclear inclusions, thereby restricting the accessibility of misfolded proteins to Hsp70 and preventing the exhaustion of limited Hsp70 resources. Therefore, in yeast, sequestrase mutants show negative genetic interactions with double mutants lacking the Hsp70 co-chaperone Fes1 and the Hsp104 disaggregase (fes1 hsp104, ) and suffering from low Hsp70 capacity. Growth of btn2 mutants is highly temperature-sensitive and results in proteostasis breakdown at non-permissive temperatures. Here, we probed for the role of the UPS system in maintaining protein homeostasis in btn2 cells, which are affected in two major PQC branches. We show that btn2 cells induce expression of diverse stress-related pathways including the UPS to counteract the proteostasis defects. UPS dependent degradation of the stringent Hsp70 substrate firefly Luciferase in the mutant cells mirrors such compensatory activities of the PQC system. Surprisingly however, the enhanced UPS activity does not improve but aggravates the growth defects of btn2 cells. Reducing UPS activity in the mutant by lowering the levels of functional 26S proteasomes improved growth, increased refolding yield of the Luciferase reporter and attenuated global stress responses. Our findings indicate that an imbalance between Hsp70-dependent refolding, sequestration and UPS-mediated degradation activities strongly affects protein homeostasis of Hsp70 capacity mutants and contributes to their severe growth phenotypes.